American Politics and the Environment, Second Edition - Daynes, Byron W. (SUNY Press Open Access, 2016)
Changing our environmental policy has been at the forefront of many political discussions. But how can we make this change come about? In American Politics and the Environment, Second Edition, Byron W. Daynes, Glen Sussman and Jonathan P. West argue it is critical that we must understand the politics of environmental decision making and how political actors operate within political institutions. Blending behavioral and institutional approaches, each chapter combines discussion of an institution along with sidebars focusing on a particular environmental topic as well as a personal profile of a key decision maker. A central focus of this second edition is the emergence of global climate change as a key issue. Although the scientific community can provide research findings to policy makers, politics can create conflicts, tensions, and delays in the crafting of effective and necessary environmental policy responses. Daynes, Sussman, and West help us understand the role of politics in the policy making process and why institutional players such as the president, Congress, and interest groups succeed or fail in responding to important environmental challenges.